A Case of Dissection and Rupture of the Innominate Artery in Acute Type A Aortic Dissection - Tamura, Kentaro (Ann Vasc Dis, 2016)
We report the case of a 59-year-old male presenting with dissection and rupture of the innominate artery with acute type A aortic dissection. We performed total arch replacement via median sternotomy with extension into the right side of the neck. The innominate artery was reconstructed just proximal to the bifurcation of the right subclavian artery and common carotid artery using the 1st limb of a 4-branched graft. This case illustrates an unusual aspect of an isolated innominate artery rupture in the absence of aortic rupture in acute type A aortic dissection.